Aktualiasasi Pemikiran KH. M. Hasyim Asy'ari Kenegaraan dan Kebangsaan: AKTUALISASI PEMIKIRAN KH. M. HASYIM ASY’ARI KENEGARAAN DAN KEBANGSAAN - Chusnul Chotimah (INOVATIF: Jurnal Penelitian Pendidikan, Agama, dan Kebudayaan, 2017)
Thought KH. M. Hasyim Asyari is reflected in some of his attitudes and writings. The story of the beginning of the establishment of Nahdatul Ulama 'can be an example of how KH. M. Hasyim Asyari has taken a decision or the initial idea of ​​the establishment of this NU. It is said that it came from KH. Wahab Hasbullah who is one of his students. Thought KH. M. Hasyim Asyari, whose knowledge is broad and his services and spiritual strength is indistinguishable, knows who and how his thoughts are. He knows very well about politics and he also has patriotism which then underlies the revision of spirit.